Load sharing characteristic of a power-integrated gearbox in a hydraulic top-drive system. (September 2019) - Sun, Youhong; Shi, Yuanling; Yao, Zongwei; Wang, Qingyan
With the increase in drilling depth, a slight conical pendulum movement of drilling strings causes the external drilling load becoming a non-negligible excitation source. The phenomenon of unique load sharing would be generated by irregular external load, which has complex influence on cyclic and axial symmetry of a power integrated gearbox. Bearing wear, which brings high frequency unpredictable vibration into the transmission system, is likely to occur because of the specific drive mode of the hydraulic top-drive system applied in well drilling. A systematic model combining the finite element method and the multi-body dynamics of a power-integrated gearbox simulation system is developed in this study with the characteristics of the power system, external load, driving forces, gear mesh stiffness, and bearing support stiffness taken into consideration. The load sharing characteristics of the power-integrated gearbox in a hydraulic top-drive system are numerically investigated. Moreover, the effects of gear mesh stiffness, bearing support stiffness, lateral load, and bearing clearance on the load sharing characteristics are systematically examined. Analysis results show that the dynamic process must be considered to achieve a comprehensive evaluation of the load sharing characteristics of a power-integrated gearbox. Evaluation results indicate that lateral load is the factor that influence the load sharing factor of the power-integrated gearbox most significantly, based on which, predictions can be safely made so that some additional mechanisms might be a practical option to diminish that effect.